2009
DOI: 10.1097/eja.0b013e32832a235c
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of insulin resistance as assessed by homeostatic model assessment index in the acute phase of myocardial infarction in nondiabetic patients submitted to percutaneous coronary intervention

Abstract: In nondiabetic STEMI patients submitted to percutaneous coronary intervention, insulin resistance, as assessed by HOMA index, is quite common and helps in the early prognostic stratification, as it represents an independent predictor of in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 35 publications
4
72
0
2
Order By: Relevance
“…In our hospital, in Florence, the reperfusion strategy of STEMI patients is represented by primary PCI [14][15][16][17][18][19]. STEMI patients are first evaluated by the Medical Emergency System staff in the prehospital setting and then directly admitted to the catheterization laboratory or transferred to it after rapid stabilization in First Aid.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In our hospital, in Florence, the reperfusion strategy of STEMI patients is represented by primary PCI [14][15][16][17][18][19]. STEMI patients are first evaluated by the Medical Emergency System staff in the prehospital setting and then directly admitted to the catheterization laboratory or transferred to it after rapid stabilization in First Aid.…”
Section: Study Populationmentioning
confidence: 99%
“…On ICCU admission, after PCI, the following parameters were measured in a fasting blood sample: glucose (mg/dl), insulin values (mIU/l) [15,17], glycated hemoglobin (HbA1c, %), troponin I (ng/ml), C-reactive protein (mg/dl) (normal values \9), alanine aminotransferase (ALT, UI/l), aspartate amino transferase (AST, UI/l) [22], NT-pro brain natriuretic peptide (NT-pro BNP) (pg/ml) [18], total cholesterol (mg/dl), triglycerides (mg/dl), HDL (mg/dl), LDL (mg/dl), and fibrinogen (mg/dl). Creatinine (mg/dl) was also measured in order to calculate the glomerular filtration rate (eGFR, ml/min/1.73 m 2 , MDRD formula) [23].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…HOMA was calculated according to the following formula: {[fasting insulin (microU/ml)] 9 [fasting glucose (mmol/l)]}/22.5 [27]. Subjects whose values exceeded the sex-specific 75th percentile (i.e., 1.80 for women and 2.12 for men) were considered to have insulin resistance (HOMA-IR) [14,28].…”
Section: Definition Of Insulin Resistancementioning
confidence: 99%
“…In non-diabetic STEMI patients undergone PCI, we reported that insulin resistance, as assessed by HOMA index, is quite common and helps in the early risk stratification, since it represents an independent predictor for in-hospital mortality [14]. Thus, the glycometabolic response to acute myocardial ischemia appears to be quite complex and, so far, poorly understood.…”
Section: Introductionmentioning
confidence: 99%